The Potential Role of the Early Maladaptive Schema in Behavioral Addictions Among Late Adolescents and Young Adults - Aloi, Matteo; Verrastro, Valeria; Rania, Marianna; Sacco, Raffaella; Fernández-Aranda, Fernando; Jiménez-Murcia, Susana; De Fazio, Pasquale; Segura-Garcia, Cristina (Frontiers in Psychology, 2020)
Background: Behavioral addiction (BA) is a recent concept in psychiatry. Few studies have investigated the relationship between BA and early maladaptive schemas (EMSs). EMS is the core of Schema Therapy (ST). According to the ST model, psychiatric disorders result from the developmentof EMSs in response to unmet emotional needs in childhood. Bach and colleagues (2018) grouped the 18 EMSs in four domains: 1) disconnection and rejection; 2) impaired autonomy and performance; 3) excessive responsibility and standards; and 4) impaired limits. This study aims at assessing the possible association of the most frequent BAs with EMSs in a large group of late adolescents and young adults and to evaluate their self-perceived quality of life. Methods: A battery of psychological tests assessing food addiction (FA), gambling disorder (GD), internet addiction (IA) and quality of life (QoL) was administered to 1,075 late adolescents and young adults (N=637; 59.3% women). A forward-stepwise logistic regression model was run to identify which variables were associated with behavioral addictions. Results: FA was more frequent among women and GD among men, while IA was equally distributed. Regarding the EMSs, participants with FA or IA showed significantly higher scores on all four-schema domains, whereas those with GD exhibited higher scores on impaired autonomy and performance and impaired limits. Besides, average scores of all domains increased with the association of 2 or more comorbid BAs. Self-perceived QoL was lower for participants with FA and IA, but not for those with GD; the presence of comorbid BAs was associated to lower PCS and MCS scores. Finally, specific EMS domains and demographic variables were associated with each BA. Conclusions: Late adolescents and young adults with FA or IA have a lower perception of their mental and physical health. The most striking result is that FA appears to be associated with the disconnection and rejection schema domain, IA with all the schema domains (except for impaired autonomy and performance), and GD with impaired autonomy and performance schema domain. In conclusion, our findings suggest that EMS should be systematically assessed during psychotherapy of patients with BAs.